Experimental Analysis on Martensite Formation of Low Carbon Steel During Rapid Cooling Process - Mohd Zaidi, Sidek; Nur Adjla, Mohamad Hafizin; Ahmad Nasser, Mohd Rose; Khairul Azha, Abd Jalal (2013)
Rapid cooling is one of the heat treatment techniques, which has been adopted in manufacturing sheet metal forming products such as structural beam and automotive parts. It involves heating of the carbon steel, and then followed by fast cooling process inside the cooling medium such as water and oil. Formation of martensites is beneficial to obtain stronger products. At present, it is most not really known how material thickness affecting martensite formation. Therefore, this study was conducted to study martensite formations inside low carbon steel for three selected part thicknesses; i.e 2, 4 and 6mm. Mild steel is one of engineering material that has been selected in this project which mostly used in many structural and vehicle components and other domestic applications [Machado, et al.]. At high temperature condition, material characteristic performs differently in comparing to normal room condition. Microstructure transformation is their advantage, in term of lower working force and higher material flow rate deformation. Top of that, it is able to produce high strength material, with an addition of a heat treatment process [Adnan, 2005]. Heat treated components can be extensively improved due to microstructure recrystalizations in rapid cooling process. It is known that carbon steels can be processed differently. From the previous studies, it was revelaed that the diffusionless transformations contribute to martensite formation which is the hardest microstructure in iron-carbon system [Wen et al., 2005]. The lowest hardness is obtained due to a diffusion transformation, which cause the ferrite and/or pearlite formation by a eutectoid reaction. Martensite is obtained during rapid cooling while ferrite and pearlite obtained from austenite during slow cooling near the equilibrium. On the other hand, with the applied cooling rate increasing, the transformed structure evolves from granular bainite, lower bainite, self-tempered martensite, to finally martensite without self tempering [Qiao et al., 2009].